The Impact of Hybrid Education in Sheng Performance Instruction - Xinyu, Wang; Sondhiratna, Thanyawat (Asia Pacific Journal of Religions and Cultures, 2024)
In the digital age, with the rapid development of internet technology and information technology and the widespread use of various smart terminals, new paradigms of knowledge construction and lifestyles have emerged, redefining knowledge construction and lifestyles. This transformation is affecting various industries, particularly in the field of education. In recent times, to adapt to the needs of music composition and performance, artists specializing in the Sheng have undertaken a series of reforms to the traditional instrument. The modified Sheng has extended its tonal range and introduced additional semitones. As a result, it is not only capable of performing traditional compositions but can also tackle Western adaptations and high-difficulty contemporary pieces. This article presented 1) The Application of Hybrid Education in Music Education, 2) The Impact of Hybrid Education in Sheng Performance Instruction, and 3) The Effectiveness of Hybrid Education in Sheng Music Education.